A comparison of back squat & safety squat bar on measures of strength, speed, and power in NCAA Division I baseball players - Meldrum, R.; DeBeliso, M. (International Journal of Sports Science, 2018)
Squat exercise variations are considered a cornerstone of resistance training (RT) programs. Understanding the effectiveness of differing squat exercise variations is important for coaches and athletes in order to optimizing the effectiveness of a RT program. Purpose: The current investigation examined a comparison of the standard Olympic barbell loaded back squat (BS) with a squat performed with the safety squat bar (SSB). Methods: Twenty eight Division I male baseball players (19.2±1.1 years, 182.5±5.6 cm, 87.6±5.1 kg) participated in a RT program comprised of two workout sessions a week for nine weeks, performing either a BS or SSB utilizing an autoregulatory progressive resistance periodization, concurrent with their existing, season-specific, resistance training program. Pitchers (n=14) utilized the SSB bar with the goal of minimizing stress on the shoulder and elbow joints during the execution of the squat. The non-pitchers (n=14) performed the Olympic barbell BS. Lower body strength (estimated 1RM squat), sprint speed (54.86 m sprint), and vertical jump (VJ cms) were assessed prior to and following the RT training period. Results: Both the VJ and estimated 1RMs had a significant positive improvement from pre-training to post-training for both the BS and SSB groups (p0.05). However, the 1RM squat gain score for the SSB was significantly greater than the BS group (pDiscussion: Given that both squat modalities yielded approximately equal improvements in VJ and lower body strength, coaches and athletes can consider the SSB variation of the squat as a viable option for developing lower body strength and power when an Olympic barbell may be contraindicated because of an upper body injury.